Access to health care, medical progress and the emergence of the longevity gap: A general equilibrium analysis - Frankovic, Ivan; Kuhn, Michael (The journal of the economics of ageing, 2019)
We study skill- and income-related differences in the access to health care as drivers of longevity inequality from a theoretical life-cycle as well as from a macroeconomic perspective. To do so, we develop an overlapping generations model populated by heterogeneous agents subject to endogenous mortality. We model two groups of individuals for whom differences in skills translate into differences in income and in the ability to use medical technology effectively in curbing mortality. We derive the skill- and age-specific individual demand for health care based on the value of life, the level of medical technology and the market prices. Calibrating the model to the development of the US economy and the longevity gap between the skilled and unskilled, we study the impact of rising effectiveness of medical care in improving individual health and examine how disparities in health care utilisation and mortality emerge as a consequence. In so doing, we explore the role of skill-biased earnings growth, skill-bias in the ability to access state-of-the art health care and to use it effectively, and skill-related differences in health insurance coverage. We pay attention to the macroeconomic feedback, especially to medical price inflation. Our findings indicate that skill-bias related to the effectiveness of health care explains a large part of the increase in the longevity with earnings-related differences in the utilisation of health care taking second place. Both channels tend to be reinforced by medical progress.